Selective uptake of HDL cholesteryl esters and cholesterol efflux from mouse peritoneal macrophages independent of SR-BI - May Brundert; Joerg Heeren; Mukaddes Bahar-Bayansar; Anne Ewert; Kathryn J. Moore; Franz Rinninger (Journal of Lipid Research, 2006)
Scavenger receptor class B type I (SR-BI) mediates the selective uptake of HDL cholesteryl esters (CEs) and facilitates the efflux of unesterified cholesterol. SR-BI expression in macrophages presumably plays a role in atherosclerosis. The role of SR-BI for selective CE uptake and cholesterol efflux in macrophages was explored. Macrophages and HDL originated from wild-type (WT) or SR-BI knockout (KO; homozygous) mice. For uptake, macrophages were incubated in medium containing 125I-/3H-labeled HDL. For lipid removal, [3H]cholesterol efflux was analyzed using HDL as acceptor. Selective uptake of HDL CE ([3H]cholesteryl oleyl ether − 125I-tyramine cellobiose) was similar in WT and SR-BI KO macrophages. Radiolabeled SR-BI KO-HDL yielded a lower rate of selective uptake compared with WT-HDL in WT and SR-BI KO macrophages. Cholesterol efflux was similar in WT and SR-BI KO cells using HDL as acceptor. SR-BI KO-HDL more efficiently promoted cholesterol removal compared with WT-HDL from both types of macrophages. Macrophages selectively take up HDL CE independently of SR-BI. Additionally, in macrophages, there is substantial cholesterol efflux that is not mediated by SR-BI. Therefore, SR-BI-independent mechanisms mediate selective CE uptake and cholesterol removal. SR-BI KO-HDL is an inferior donor for selective CE uptake compared with WT-HDL, whereas SR-BI KO-HDL more efficiently promotes cholesterol efflux.